Techno-economic analysis of advanced small modular nuclear reactors - Asuega-Souza, Anthony, author; Quinn, Jason, advisor; Simske, Steve, committee member; Bandhauer, Todd, committee member (Colorado State University. Libraries, 2022)
Small modular nuclear reactors (SMRs) represent a robust opportunity to develop low-carbon and reliable power with the potential to meet cost parity with conventional power systems. This study presents a detailed, bottom-up economic evaluation of a 12x77 MWe (924 MWe total) light-water SMR (LW-SMR) plant, a 4x262 MWe (1,048 MWe) gas-cooled SMR (GC-SMR) plant, and a 5x200 MWe (1,000 MWe total) molten salt SMR (MS-SMR) plant. Cost estimates are derived from equipment costs, labor hours, material inputs, and process-engineering models. The advanced SMRs are compared to natural gas combined cycle plants and a conventional large reactor. Overnight capital cost (OCC) and levelized cost of energy (LCOE) estimates are developed. The OCC of the LW-SMR, GC-SMR, and MS-SMR are found to be $4,844/kW, $4,355/kW, and $3,985/kW respectively. The LCOE of the LW-SMR, GC-SMR, and MS-SMR are found to be $89.6/MWh, $81.5/MWh, and $80.6/MWh respectively. A Monte Carlo analysis is performed, for which the OCC and construction time of the LW-SMR is found to have a lower mean and standard deviation than a conventional large reactor. The LW-SMR OCC is found to have a mean of $5,233/kW with a standard deviation of $658/kW and a 90% probability of remaining between $4,254/kW and $6,399/kW, while the construction duration is found to have a mean of 4.5 years with a standard deviation of 0.8 years and a 90% probability of remaining between 3.4 and 6.0 years. The economic impact of economies of scale, simplification, modularization, and construction time are evaluated for SMRs. Policy implications for direct capital subsidies and a carbon tax on natural gas emissions are additionally explored.
Keywords: techno-economic analysis; small modular reactors